LUQATHAH DALAM PERSPEKTIF HADIS - Muhammad Uchaida Sabilil Matin (LPPM Universitas Cipta Mandiri, 2026)
This study examines the concept of luqathah (found property) from the perspective of hadith, focusing on the analysis of authenticity and interpretation through the method of takhrij al-hadith. Luqathah, as found property, has legal and ethical implications closely related to the values of trustworthiness, social responsibility, and the protection of ownership rights in Islam. This research aims to trace the hadiths that form the legal basis of luqathah, analyze the quality of their chains of transmission (sanad) and texts (matan), and explain their normative implications in Islamic jurisprudence. The findings indicate that the hadiths concerning luqathah, particularly those recorded in Sahih al-Bukhari, meet the criteria of authentic (sahih) hadiths with continuous chains and clear meanings. This study confirms that the Islamic regulation of found property is grounded in principles of caution, honesty, and public benefit, making it relevant to contemporary social contexts and character education.